Study on the flow and diffusion behavior of coal gangue slurry in subsequent space after mining: physical and numerical simulation - Liu, Hengfeng; Guo, Jiahao; Rodriguez-Dono, Alfonso; Topal, Erkan; Feng, Jianye; Li, Xinying; Wang, Xiao; Zhao, Heng (Frontiers in Environmental Science, 2025)
The application of grouting backfill technology in the Subsequent Space after Mining (SSM) in coal mines effectively addresses the dual challenges of coal-based solid waste disposal and surface subsidence control. However, the SSM, often likened to a geological “black box,” is difficult to visualize, which severely hinders the widespread application of this technology. This study overcomes this challenge by using a self-developed two-dimensional visual physical simulation system for sealed grouting in the SSM, which has been validated through numerical simulation. This system enables visualization and precise quantitative analysis of the flow and diffusion behavior of coal gangue slurry within the SSM. The results indicate that as the working face advances, the SSM undergoes a dynamic evolution involving fracture development, separation layer formation, and eventual roof collapse. This process leads to a maximum roof subsidence of 5.51 m and the formation of 16 stable fracture zones. Among these, the fracture network formed by zones T7# to T10# and L1# to L6# serves as the key SSM for slurry accommodation and effective backfilling. The spread of the coal gangue slurry is primarily controlled by the connectivity of the fracture network, demonstrating notable spatiotemporal variation. In fractures T1# to T6#, the slurry exhibits an “oval-spindle” diffusion morphology with a gradually declining flow rate over time. In contrast, within fractures T7# to T10# and L1# to L6#, the slurry migrates in a “top-to-bottom” and “right-to-left” pattern without a reduction in diffusion rate. Furthermore, the grouting horizon is identified as the most influential factor on the slurry’s diffusion range, followed by grouting pressure, while slurry concentration has the least impact. The optimal levels for the three factors—grouting pressure, grouting layer, and slurry concentration—are Level 3 (0.8 MPa), Level 3 (T1#- T10#, L1#- L6#), and Level 1 (60%), respectively.